Let's look at 5(2-j) + (2j-3). I'll insert the implied multiplication sign to write 5 x (2-j) + (2j-3). We do the multiplication first (BODMAS). 5 x (2-j): multiplication distributes over addition, that is, a x (b+c) = (a x b) + (a x c), inserting () for clarity. Equally x distributes over -. So 5 x (2-j) = 5x2 - 5xj = 10 - 5j. So the total expression is (10 - 5j) + (2j - 3). We can gather terms (repeatedly using associative and commutative properties) to get (2j-5j) + (10-3). Reversing the distributive law 2j-5j = (2-5)j = -3j. So the answer is7 - 3j.